Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1007/bf01116000
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipoprotein binding and uptake by hepatocytes during rat liver regeneration

Abstract: The binding and uptake of cholesterol enriched lipoproteins by isolated hepatocytes was decreased at 16 hours after partial hepatectomy, with a tendency to return to control values as the regeneration proceeds. The number of lipoprotein binding sites of total cellular membranes remained similar to control at 16 and 24 hours. The plasma lipoprotein pattern, determined by electrophoretic analysis, showed a lower per cent of very low density lipoproteins (VLDL) and a higher per cent of low density lipoproteins (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Partial liver resection resulted in a marked decrease in the concentration of VLDL lipid components, particularly triacylglycerol. These data are in agreement with those of Trentalance et al [10], who reported a decrease of plasma VLDL by approx. 50 % at 16 h after surgery.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Partial liver resection resulted in a marked decrease in the concentration of VLDL lipid components, particularly triacylglycerol. These data are in agreement with those of Trentalance et al [10], who reported a decrease of plasma VLDL by approx. 50 % at 16 h after surgery.…”
Section: Discussionsupporting
confidence: 94%
“…In view of the discrepancies mentioned above (ref. [10] versus refs. [4,5]), we also measured lipid content and composition of the major lipoproteins (VLDL, LDL and HDL) as a function of post-surgery time.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Its expression was reported as significantly up-regulated in serum of patients diagnosed with DILI but not in those with non-alcoholic steatohepatitis [20,23]. Early work had shown transcriptional and posttranscriptional regulation of ApoE, ApoA1 and ApoA2 in liver tissue at various pathophysiological states [40] and changes in lipoprotein binding and uptake by hepatocytes during rat liver regeneration [41]. In a proteomic investigation of drug-induced steatosis a moderate but statistically significant up-regulation of ApoE was observed in rat liver, further documenting its prognostic value in predicting DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various metabolic processes that take place during hepatic regeneration some parameters of lipid metabolism have been reported : the rate of esterification of fatty acids from adipose tissue is higher, lipogenesis is increased [8], capacity to take up circulating lipoproteins is reduced, and lecithin cholesterol acyltransferase (LCAT) activity is low. Liver regeneration is also associated with a reduction in plasma levels of very-lowdensity lipoprotein (VLDL) and an increase in the levels of lowdensity lipoprotein (LDL) [9]. In order for the liver to be able to regain its complete functionality and regenerate its mass, contributions of metabolic precursors from other tissues are required.…”
Section: Introductionmentioning
confidence: 99%